(untitled) (Research, Society and Development, 2020)
The objective of this work was to evaluate the antifungal activity of the essential oil of Cymbopogon citratus in the control of Aspergillus brasiliensis in analysis in vitro and in stored corn kernels. Two in vitro tests were carried out. One of them, by diffusion in agar and the other by microdilution in wells. The concentrations used for the agar diffusion assay were 0.2; 0.4; 0.6; 0.8 and 1.0 µL mL-1. The concentrations used for the microdilution test were: 0.1; 0.2; 0.3; 0.4; 0.5; 0.6; 0.7; 0.8; 0.9; 1.0 and 1.2 µL mL-1. The mycelial growth was evaluated over time, using the Scott-Knott test at 5% significance. From the results obtained, it was verified that the application of the essential oil of Cymbopogon citratus interferes significantly in the fungal development of the species Aspergillus brasiliensis. The microdilution test in wells was used in a qualitative way, indicating absence of growth in doses from 0.8 µL mL-1. For the corn grain test, the essential oil dosages of 0.5; 0.8 and 1.0 µL mL-1 and were stored for 42 days. There was no significant difference in the different doses of essential oil over the storage period for this assay.